1983
DOI: 10.1002/sia.740050504
|View full text |Cite
|
Sign up to set email alerts
|

Laser microprobe mass analysis (LAMMA) and adsorption study of aliphatic alkylammonium ions and alkylamines on asbestos fibre surfaces

Abstract: The adsorption-desorption behaviour of aliphatic alkylamines for asbestos was studied. A high affinity and strong adsorption characteristics, controlled by Van der Waals interaction and steric hindrance were obtained. For the R.N€I-.CI (1 < n C 4) doped asbestos fibres, the laser microprobe mass analysis (LAMMA) technique was used to analyse selectively the individual asbestos surface loadings. Only for quaternary (and tertiary at higher concentrations) ammonium products, could a semi-quantitative picture of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In previous work it was shown that the use of laser desorption operating conditions (10)(11)(12)(13)(14)(15) in LAMMA results in the ready detection of adsorbed organic constituents. Benzidine, iV,jV-dimethylaniline (DMA), and benzo[a]pyrene (BaP) were adsorbed in the laboratory on the U.I.C.C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous work it was shown that the use of laser desorption operating conditions (10)(11)(12)(13)(14)(15) in LAMMA results in the ready detection of adsorbed organic constituents. Benzidine, iV,jV-dimethylaniline (DMA), and benzo[a]pyrene (BaP) were adsorbed in the laboratory on the U.I.C.C.…”
Section: Resultsmentioning
confidence: 99%
“…Asbestos fibers can be held onto a Formvar film fixed to a standard copper electron microscope grid. Organic impurities adsorbed onto the surface of asbestos fibers can be detected at low laser irradiance, in the laser desorption (LD) mode (10)(11)(12)(20)(21)(22). For details on sample preparation for LAMMA analysis we refer to De Waele et al (11).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chrysotile's adsorption of benzo [a]pyrene, a component of cigarette smoke with mutagenic and carcinogenic potential, has been studied extensively (Shabad et al 1974;Krivosheeval and Pylev 1974;Lakowicz and Bevan 1980;De Waele et al 1983a;Menard et al 1986aMenard et al , 1986bGerde and Scholander 1988;De Waele and Adams 1988). The chrysotile's adsorption of other polycyclic hydrocarbons (Menard et al 1986b;Craighead 1981, 1982;Fournier and Pezerat 1986), both aliphatic and aromatic amines (De Waele et al 1983a, 1983bDe Waele and Adams 1988;De Waele, Vansant, and Adams 1983), benzene (Gorski and Stettler 1975), and basic and acidic dyes -including picric acid (Valerio, Puntoni, and Santi 1979) -has also been investigated.…”
Section: Introduction Backgroundmentioning
confidence: 99%